The novel ATM inhibitor (AZ31) enhances antitumor activity in patient derived xenografts that are resistant to irinotecan monotherapy - Greene, Justin (Oncotarget, 2017)
Irinotecan, a standard of care therapy for CRC, elicits cytotoxic effects by generating double strand breaks resulting in DNA damage. The activation of the ATM pathway plays a fundamental role in regulating the cellular response and repair to DNA damage. The objective of this preclinical study was to determine whether ATM inhibition would enhance sensitivity to irinotecan treatment. Treatment effects of AZ31, irinotecan or AZ31 + irinotecan were investigated in CRC cell lines and CRC patient derived xenografts. Activation of ATM and downstream targets p-RAD50 and p-H2AX were evaluated by immunohistochemistry. Combinational effects were demonstrated in 4 out of 8 CRC explants. Interestingly, each of the combinational sensitive CRC PDX models were shown to be more resistant to irinotecan single agent therapy. Treatment with irinotecan significantly elevated the ATM pathway evident by an increase in the activation of H2AX and RAD50. Combinational therapy reduced the activation of H2AX and RAD50 when compared to irinotecan alone in the combination sensitive CRC098. AZ31 + irinotecan was effective at reducing tumor growth in tumors that exhibited resistance to irinotecan in our CRC PDX model. These findings support further investigation of this combinational therapy for the treatment of CRC patients.